Prestasi Alat Pendingin Termoakustik Dengan Variasi Bentuk Stack - Mitha Tri Indraswari; Dinni Agustina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The use of conventional cooling machines that have an impact on the environment because it uses refrigerant gas containing CFC and HFC gases that are harmful to the atmosphere. One alternative to the cooling machine is a thermoacoustic cooling system. The thermoacoustic cooling system is a system that converts high-amplitude sound waves into heat energy which produces temperature changes. This system is called environmentally friendly because it uses air conditioning or noble gas cooling media. The main components of the thermoacoustic system are the resonator tube, the stack, the working fluid and the loudspeaker. In this study the working fluid used is air. The shape of the stack and stack position affect the performance of the cooling device. Thermoacoustic cooling devices using a stack of mica plastic material with a thickness of 0.5 mm and a length of 9 cm have been designed and operated on a resonator tube with a diameter of 5 cm and a length of 60 cm. The test was carried out experimentally using a loudspeaker sound source at a resonant frequency of 145 Hz. The ability of the cooling device based on results of the stack plate parallel produces a temperature difference at both ends of the stack of 4.31OC at 28OC ambient temperature. Keywords:Thermoacoustic, cooling device, COP